Potential Use of CRISPR/Cas13 Machinery in Understanding Virus–Host Interaction - Bayoumi, Mahmoud; Munir, Muhammad (Frontiers in Microbiology, 2021)
Prokaryotes have evolutionarily acquired an immune system to fend off invading mobile genetic elements, including viral phages and plasmids. Through recognizing specific sequences of the invading nucleic acid, prokaryotes mediate a subsequent degradation process collectively referred to as the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)–CRISPR-associated (Cas) (CRISPR–Cas) system. The CRISPR–Cas systems are divided into two main classes depending on the structure of the effector Cas proteins. Class I systems have effector modules consisting of multiple proteins, while class II systems have a single multidomain effector. Additionally, the CRISPR–Cas systems can also be categorized into types depending on the spacer acquisition components and their evolutionary features, namely, types I–VI. Among CRISPR/Cas systems, Cas9 is one of the most common multidomain nucleases that identify, degrade, and modulate DNA. Importantly, variants of Cas proteins have recently been found to target RNA, especially the single-effector Cas13 nucleases. The Cas13 has revolutionized our ability to study and perturb RNAs in endogenous microenvironments. The Cas13 effectors offer an excellent candidate for developing novel research tools in virological and biotechnological fields. Herein, in this review, we aim to provide a comprehensive summary of the recent advances of Cas13s for targeting viral RNA for either RNA-mediated degradation or CRISPR–Cas13-based diagnostics. Additionally, we aim to provide an overview of the proposed applications that could revolutionize our understanding of viral–host interactions using Cas13-mediated approaches.